2018
DOI: 10.11591/edulearn.v12i1.6315
|View full text |Cite
|
Sign up to set email alerts
|

Critical Thinking in Accounting Textbooks

Abstract: A textbook is the main source of learning in many universities, yet there are only a few studies which specifically evaluate accounting textbook. This research aimed to evaluate the accounting textbooks used in some Indonesian universities and is expected to provide recommendations of accounting textbooks which are potential to develop students' critical thinking ability. This study was a content analysis. The analysis was based on the Bloom's taxonomy as well as the indicators of contextual representation int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
1
9
0
2
Order By: Relevance
“…The findings of the present research show that in the examined text, the cultivation of the critical thinking skills is not promoted sufficiently since this promotion does not occur with equal frequency per skill. This is consistent with the results of other relevant researches which examined textbooks and revealed that in their content, critical thinking is not promoted sufficiently (Khademi, 2020;Peyró et al,2020;Samiee et al, 2020;Al-Qahtani, 2019;Es-Salhi & Elfatihi, 2019;Irafahmi et al, 2018;Maki & Horita, 2018;Solihati & Hikmat, 2018;Aybek & Aslan, 2016;Sobkowiak, 2016).…”
Section: Critical Thinking Skillssupporting
confidence: 89%
“…The findings of the present research show that in the examined text, the cultivation of the critical thinking skills is not promoted sufficiently since this promotion does not occur with equal frequency per skill. This is consistent with the results of other relevant researches which examined textbooks and revealed that in their content, critical thinking is not promoted sufficiently (Khademi, 2020;Peyró et al,2020;Samiee et al, 2020;Al-Qahtani, 2019;Es-Salhi & Elfatihi, 2019;Irafahmi et al, 2018;Maki & Horita, 2018;Solihati & Hikmat, 2018;Aybek & Aslan, 2016;Sobkowiak, 2016).…”
Section: Critical Thinking Skillssupporting
confidence: 89%
“…Textbooks usage is not limited to determine the content. Other than content, texbooks have been used to determine learning objectives as well as assessment (Irafahmi, Nuris, Zahroh, & Nagari, 2018). Given the importance of the role of a textbook, it is not surprising that all studies in this scoping review determine the types of auditing topics based on the list of topics in popular auditing textbooks, such as books by Arens, Louwers, and Messier.…”
Section: The Relevance Of Auditing Education From the Aspect Of Contentmentioning
confidence: 99%
“…An integrated case approach is recommended to replace the old model. In this approach, evaluation can be carried out on aspects of students' communication skills, critical thinking, and decision analysis, as well as mastery of quantitative aspects of accounting (Derstine, Emig, & Grant Sr, 2015;Irafahmi, Nuris, Zahroh, & Nagari, 2018).…”
Section: Introductionmentioning
confidence: 99%